Pengembangan Media Video Animasi Berbasis Powtoon pada Tema 1 Subtema 1 Pembelajaran 2 - Ramadhan, Muhammad Islah (STKIP Andi Matappa Pangkep, 2024)
This research aims to determine the development of powtoon-based animation videos to be developed for class III students at SDN Cibinong 1 and to determine the feasibility of powtoon-based animation videos for the learning process carried out in schools. The method used in this research is the ADDIE method which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. In this research, validation tests were carried out on experts, namely media experts, language experts and material experts. The validation results from media experts obtained 100% with very feasible criteria. Linguist validation results obtained as much as 80% with appropriate criteria. And the material expert validation results were 90% with very feasible criteria. The results of the student response questionnaire were 90.2% with very adequate criteria. These results show that the powtoon-based animation video in theme 1 sub-theme 1 learning 2 is proven to be valid, interesting, innovative and very suitable for use in the learning process.